What factors drive heterogeneity of preferences for micro-health insurance in rural Malawi? - Abiiro, Gilbert Abotisem; De Allegri, Manuela (Health policy and planning, 2016)
Investigating the factors that drive differences in preferences for health insurance products among rural populations is a relevant policy issue that has so far received little attention. This study used a discrete choice experiment to explore heterogeneity of preferences for a prospective micro-health insurance (MHI) product in Malawi. Through an extensive qualitative study, six attributes, each associated with three levels, were derived and used to construct a D-efficient design. The attributes included unit of enrollment, management structure, health service benefit package, copayment levels, transportation coverage and monthly premium. The experiment was interviewer administered to a stratified random sample of household heads and their spouse(s). Using mixed logit and generalized multinomial logit models, respondent characteristics were interacted with MHI attributes to explore heterogeneity of preferences. The results showed that those in the higher age group (≥55 years) and those from households with higher household expenditure had significantly higher preferences for comprehensive and medium benefit packages than for a basic package. Those from households that incurred any healthcare expenditure within the past 4 weeks had lower preferences for the core family as a unit of enrollment than the individual, and higher preferences for coverage of transport costs. Women and non-micro-finance members had higher preferences for 25% copayment than for 50% copayment. There was evidence of scale heterogeneity signifying that the observed preference variations could have resulted from scale and variance differences, rather than real variations in the taste of respondents. To attract the relatively older and wealthier, prospective MHI should offer comprehensive health services benefit packages. Premium exemptions or subsidies should also be offered to the poor. Lower copayments can provide an incentive for women and non-micro-finance members, whilst coverage of transport costs can also attract those with recent history of incurring out-of-pocket healthcare expenditure to accept MHI.